Androgen receptor polymorphisms and testicular cancer risk. (2nd September 2014) - Grassetti, D.; Giannandrea, F.; Paoli, D.; Masciandaro, P.; Figura, V.; Carlini, T.; Rizzo, F.; Lombardo, F.; Lenzi, A.; Gandini, L.
Summary: Testicular cancer (TC) is currently the most common malignant solid tumour in Caucasian males aged 15–39 years. Epidemiological evidence suggests that its onset may be due to an imbalance in the action of steroidal sex hormones and their receptors. A faulty androgen receptor signalling pathway can, in fact, cause various male reproductive disorders. The androgen receptor (AR) gene has two polymorphic segments consisting of CAG and GGC repeats. The length of CAG repeats has been shown to affect the regulation of AR activity. In our study, we used fragment analysis to evaluate the AR gene repeats of 302 TC patients and 322 controls, to establish if there is any association between repeat number and TC. This study of the largest Italian caseload investigated to date highlighted three particularly significant aspects. First, a CAG repeat number of ≥25 may be considered a risk factor for the onset of TC, given its greater frequency in patients in comparison with controls. This difference became significant for the non‐seminoma group. Second, men with CAG repeats below 21 or above 24 were found to have a, respectively, 50 and 76% higher risk of TC than those with CAG 21–24, suggesting that these too can be considered a risk factor for TC. Finally, stage II patients were more likely to have a CAG repeat number <21 or >24 than stage I patients.